Răspunsuri

2014-03-23T11:56:30+02:00
5,
b) xpatrat + 5x + 4 = xpatrat + 4x + x + 4= x(x+1) + 4(x+1)=(x+4)(x+1)
f) xpatrat + 9x + 20 = xpatrat  + 5x + 4x + 20 = x(x+5) + 4(x+5)= (x+4)(x+5)
j) xpatrat + 15x + 36 = xpatrat + 12x+3x+36 = x(x+3) + 12(x+3) = (x+12)(x+3)
h)xpatrat + 13x + 42 = xpatrat + 7x + 6x +42 = x(x+6) + 7(x+6) = ( x+6)(x+7)

6.
b)xpatrat - 7x +12 = xpatrat - 3x - 4x + 12 = x(x-3) -4 ( x-3) = (x-4)(x-3) 
f)xpatrat - 9x +14= xpatrat - 7x - 2x +14=x(x-2) -7(x-2)=(x-7)(x-2)
j)xpatrat - 5x + 4 = xpatrat -x - 4x + 4 =x(x-1)-4(x-1)= (x-4)(x-1)